Digging the river: the historical geography of the Amstel area (800–1275 AD). Issue 4 (16th January 2015) - de Bont, C.
Abstract: Around 800 AD the peatlands around Amstelland were drained by two rivers. The 'northern' Amstel discharged surplus water directly into Lake Almere, which from the 12th century onwards was enlarged to form the Sudersee (in Dutch: Zuiderzee). The 'southern' Amstel was a near-abandoned westernmost arm of the River Vecht discharging the poorly drained borderland around the river Vecht into Lake Almere/the Sudersee. As part of the reclamation of peatlands associated with agricultural activities between the end of the 10th and the mid-13th centuries, the rivers were connected via a canal, thus creating the river Amstel, as it is known today.